Development of the Heart Failure Screening Tool (Heart-FaST) to measure barriers that impede engagement in self-care. (October 2014) - Cameron, Jan; Ski, Chantal F; McLennan, Skye N; Rendell, Peter G; Whitbourn, Robert J; Thompson, David R
Background: Screening for self-care capacity is advocated before applying educational strategies. No screening tool has been specifically developed to assess barriers that impede engagement in self-care in people with heart failure. Earlier conceptual work (InCOGNITO) identified NYHA class, mild cognitive impairment and depressive symptoms as barriers that impede engagement in HF self-care. Aims: Study aims were: 1) to develop the Heart Failure Screening Tool (Heart-FaST) as a means of assessing three critical barriers to self-care; 2) to assess the content validity of the Heart-FaST; and 3) to test the feasibility of implementing the Heart-FaST in clinical practice. Methods: The Heart-FaST was developed from barriers identified in previous research (InCOGNITO) and from expert panel consensus. Content validity was assessed by examining the proportion of experts who scored each item as relevant. Results: The InCOGNITO study indicated that four cognitive tasks, seven emotional questions and NYHA functional class were significantly correlated with the self-care scales: maintenance, management and confidence. These factors were used to create the Heart-FaST items. Consensus on wording and items to be included in the Heart-FaST was reached after two rounds of panel discussion. All items had an item-level content validity index ≥0.78. High scores on each barrier (physical, cognitive and emotional functioning) suggest poor self-care and the need for more intensive disease management efforts. Conclusion: The Heart-FaST measures three critical barriers that impede engagement in self-care. In clinical practice this tool may assist in individually tailoring educational and support strategies to promote effective heart failure self-care.